Effective Drugs Against Severe Fever With Thrombocytopenia Syndrome Virus in an in vitro Model - Bang, Mi-Seon; Kim, Choon-Mee; Kim, Dong-Min; Yun, Na Ra (Frontiers in Medicine, 2022)
Background: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease caused by the SFTS virus (SFTSV). This syndrome is endemic in China, South Korea, and Japan, with a fatality rate of approximately 20–30%. Although the World Health Organization has listed SFTS as a disease that requires urgent steps for the development of its treatment, no treatments are available. Methods: We analyzed the antiviral activity of 41 drugs against the SFTSV to explore potential therapeutic candidates using real-time reverse transcription-polymerase chain reaction and plaque assay in vitro. Results: Peramivir, nitazoxanide, and favipiravir were found to have inhibitory effects on the SFTSV at concentrations below the maximum plasma concentration (Cmax). The concentrations that inhibited the SFTSV by 50% were as follows: peramivir, half maximal effective concentration (EC50) 12.9 μg/mL; nitazoxanide, EC50 0.57 μg/mL; and favipiravir, EC50 4.14 μg/mL. Conclusions: The effects of peramivir and nitazoxanide on the SFTSV were identified for the first time in this study. Future studies need to include animal models of SFTSV infection, clinical trials including dose-ranging trials, and evaluation of combination therapy with other potential antivirals.